Invitro Antibacterial Activity Patterns of Branded and Locally Made Honey in the Treatment of Suspected Bacterial Keratitis in Ilorin (Western Journal of Medical and Biomedical Sciences, 2024)
Honey has been established as an effective antibacterial and antioxidant for millennia. However, with the alarming rise in the emergence and re-emergence of antibiotic-resistant bacteria as a growing problem and a threat to public health. There is therefore urgent need to search for alternative remedies especially among plants to combat antibacterial resistance in bacteria. The purpose of this study was to determine the invitro antibacterial activity patterns of branded and local honey samples on suspected bacterial keratitis pathogens. Twenty-four honey samples (10 branded and 14 local) were collected from different supermarkets and local markets in Ilorin. The sterility test was performed on all the honey samples by culturing them on Blood agar and incubated at 370 C in the Medical Microbiology Laboratory. The honey samples were tested for antibacterial activity against 61 clinical isolates collected from patients with suspected bacterial keratitis in Eye clinics in selected hospitals in Ilorin and tested using various culture media and disc diffusion technique in the Laboratory. The honey samples were diluted in sterile deionized water to achieve concentrations of 80, 50, 25, 12.5 and 6.25% (w/v). Different classes of commonly used antibiotics were tested against the isolates by the Kirby Bauer disc diffusion method. The inhibition zone of each antibiotic tested against each isolate was measured using graduated meter rule to determine the diameter of the inhibition zones. Sixty-one clinical isolates were identified by conventional microbiological methods. Both the branded and local honey samples exhibited antibacterial properties against tested Gram-positive and Gram-negative bacteria but the branded honey showed greater anti-bactericidal effect than local honey. Comparative susceptibility pattern of conventional antibiotics, branded and local honey samples were significant against Klebsiella pneumoniae, Citrobacter freundi, Escherichia coli, Pseudomonas aeruginosa, Serratia marcescens, Mirococcus spp, Staphylococcus aureus and uncommon pathogens (
Keywords: Antibacterial; Branded; Comparison; Honey, Inhibition; Local, Susceptible